Foglakoztatás és munkanélküliség a Dél-Dunántúl falvaiban - Rudl, József (Közép-Európai Közlemények, 2009)
The reappearance of unemployment is the outcome of the change that has happened as a result of the regime change in Hungary (around 1990) As a consequence of privatization in agriculture masses of people have become unemployed again in the countryside. Beside the present unemployed population there appeared a notable number of people who should be provided with labor shortly at low wages. A new type of farmers has made an appearance, who are not hired even for seasonal jobs, due to the technical development in agriculture. Due to unemployment the mobility of the population has strongly decreased. Earlier, before the changing of the regime, more people were crossing the borders of their microregions than today. By developing the infrastructure in the countryside the mobility of this population could be increased, evalvating the smallest villages higher.